Mulheres que amam mulheres: os desafios de inclusão das mulheres lésbicas e bissexuais no ambiente de trabalho - Rosa, Gustavo Hart da (Universidade do Vale do Rio dos Sinos, 2024)
This study aims to understand the strategies used by homo or bisexual women to confront homophobia and other prejudices in the workplace. Through a qualitative and exploratory approach, the study delves into the experiences of prejudice, the ways of manifesting sexuality at work, and the existing or absent inclusion policies within organizations. The work is grounded in a comprehensive theoretical review, discussing everything from the evolution of studies on sexual minorities within organizations to the strategic management of sexual diversity, including key concepts such as homophobia, lesbophobia, and the dynamics of power and exclusion related to gender and sexuality. The methodology involved semi-structured interviews and a focus group with homo or bisexual women, as well as interviews with managers, aiming for a broad understanding of the inclusion and exclusion dynamics experienced by these women in the corporate environment. The results indicate the persistence of multiple forms of prejudice, including sexism, lesbophobia, ageism, racism, and fatphobia, and highlight the complexity of manifesting sexuality at work, ranging from total openness to concealment due to fear of discrimination. A significant lack of specific inclusion policies for homo and bisexual women was identified, as well as a lack of structured and effective actions in company diversity policies. The dissertation proposes guidelines for more effective inclusion practices, emphasizing the importance of education and sensitization on LGBTQIAP+ issues, and the implementation of concrete actions to ensure a safe and inclusive work environment for everyone. The final considerations underline the relevance of conscious and active diversity management, which not only recognizes the existence of sexual diversity but also acts decisively to promote the effective inclusion of these individuals in the corporate environment.
Keywords: Inclusão no ambiente de trabalho; Mulheres lésbicas e bissexuais; Lesbofobia; Gestão da diversidade sexual; Preconceitos no ambiente corporativo; políticas de inclusão LGBTQIAP+; Identidade e expressão de gênero; Discriminação baseada em gênero e sexualidade; Inclusion in the workplace; Lesbian and bisexual women; Lesbophobia; Management of sexual diversity; Prejudices in the corporate environment; Gender and sexuality identity and expression; Discrimination based on gender and sexuality; ACCNPQ::Ciências Sociais Aplicadas::Administração